OPTIMALISASI PENJADWALAN DAN PENGENDALIAN PROYEK SISTEM INFORMASI MENGGUNAKAN CRITICAL PATH METHOD (CPM) DAN EARNED VALUE ANALYSIS (EVA) - Aziz Hasan Nurrahman Alqowi (2021)
Planning and controlling costs and time are part of project management to ensure the project runs well. Scheduling requires Work Breakdown Structure and Network Diagrams, the more detailed the more accurate it will be. It is also necessary to identify the critical path using the Critical Path Method. Control is carried out to prevent deviations using earned value analysis. The research was conducted on an information system project at PT. X conducted by PT. JT, which provides a more accurate baseline schedule and analyzes the earned value of project at the end of February. The results showed that the proposed baseline schedule was able to reduce 17 working days or 26 calendar days and obtained 47 critical activities. In the results of the earned value analysis obtained a delay of 7 working days with an SPI value of 0.94 and a CPI of 0.93. The deviation at the end of project is estimated at Rp 22,872,691.48 and 18 working days. After crashing, the total duration is returned according to the plan with smaller losses.